2019
DOI: 10.1101/539437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semantic coding in the occipital cortex of early blind individuals

Abstract: The visual cortex of early blind individuals is reorganized to support cognitive functions distinct from vision. Research suggests that one such prominent function is language. However, it is unknown whether the visual cortex of blind individuals codes for word meaning. We addressed this question by comparing neuronal activity evoked by a semantic decision task, using magnetoencephalography (MEG), between 12 early blind and 14 sighted participants otherwise comparable with regard to gender, age and education. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…Some prior evidence supports the idea that cortical functional specialization is somewhat more variable across blind than sighted people. Previous studies find that laterality patterns vary to a greater extent across blind than sighted people (Lane et al, 2017;Abboud et al, 2019). This could contribute to lower alignment in visual cortex in the current study.…”
Section: Inter-subject Synchrony Exceeds Spatial Pattern Alignment In the Visual Cortices Of Blind Individualsmentioning
confidence: 46%
See 2 more Smart Citations
“…Some prior evidence supports the idea that cortical functional specialization is somewhat more variable across blind than sighted people. Previous studies find that laterality patterns vary to a greater extent across blind than sighted people (Lane et al, 2017;Abboud et al, 2019). This could contribute to lower alignment in visual cortex in the current study.…”
Section: Inter-subject Synchrony Exceeds Spatial Pattern Alignment In the Visual Cortices Of Blind Individualsmentioning
confidence: 46%
“…This could contribute to lower alignment in visual cortex in the current study. Consistent with the idea of greater individual variability of cortical map across blind individuals, a recent MEG study revealed that semantic categories of auditory word stimuli were decodable from occipital cortex of blind individuals when analyses were performed at the individual-subjects level; however, cross-subject generalization was unreliable, indicating considerable variability in neural responses across blind individuals (Abboud et al, 2019). Together with prior findings, the present results provide both evidence for presence of reliable visual cortical maps across people who are blind and evidence that cortical alignment across people is somewhat reduced in blind relative to sighted people.…”
Section: Inter-subject Synchrony Exceeds Spatial Pattern Alignment In the Visual Cortices Of Blind Individualsmentioning
confidence: 75%
See 1 more Smart Citation
“…[12][13][14] No obstante, V1 tiene relación no solamente con la información auditiva y táctil, sino también con la memoria y el lenguaje. Existen diversos estudios 8,13,[15][16][17][18][19] en los cuales V1 se activa en tareas de lenguaje (ya sea mediante Braille o de forma auditiva) y memoria operativa (semántica y aritmética) con mayor intensidad en sujetos con ceguera temprana o congénita.…”
Section: Introductionunclassified
“…However, unlike association regions, the primary visual cortex of people born blind has also been shown to respond to tasks quite remote from visual processing, such as language comprehension and production (Abboud et al, 2019; Bedny et al, 2011a; Burton et al, 2003; Burton et al, 2002b; Dietrich et al, 2013; Lane et al, 2015; Röder et al, 2002). Although evidence for language activation is compelling, persuasive evidence for a mechanism by which such extreme functional reorganization might occur has not been provided to date: for example, beyond deterioration of the visual pathways (Noppeney et al, 2005; Shimony et al, 2006; Shu et al, 2009; Yu et al, 2007), no drastic differences in anatomical connectivity of the visual cortex were found between congenitally blind people and sighted controls.…”
Section: Introductionmentioning
confidence: 99%